MENGGUNAKAN PENAJAMAN CIRI QUESTIONING & CLARIFYING UNTUK MEMBELAJARKAN FUNGSI POLINOMIAL - Nila Kartika Sari (Universitas Muhammadiyah Ponorogo, 2017)
The purpose of this study was to determine the effectiveness of learning by questioning and clarifying sharpening presented with reciprocal teaching strategy, in this case it is sharpened on two characteristics of the strategy on the matter polynomial functions. In this lesson, students formed into small groups where the small group of students will each propose and clarify questions that arise. Results of questions and clarifications subsequently clarified at the front of the class, and responded to by other groups. The conclusion is a learning procedure using a sharpening feature of questioning and clarifying for students are students conducting questioning and clarifying in groups to formulate and clarify any questions and answers material polynomial, either in small groups or classes. While the impact for students is the improvement of student learning outcomes in the polynomial function that is 86.7% of the students were able to score more than or equal to 65.Kata Kunci: Fungsi Polinomial, Reciprocal Teaching, Questioning, Claryfying